Reuse of black cumin biomass into beneficial additive for thermoplastic polyurethane-based green composites with silane modifiers - Sismanoglu, Sedef; Tayfun, Ümit; Gradinariu, Petronela; Popescu, Carmen-Mihaela; Kanbur, Yasin; Tayfun, Ümit (Springer Heidelberg, 2023)
Rich in protein, carbohydrates, and lignocellulosic, black cumin is a plant that is used in the treatment of many diseases and has antioxidant and anti-tumor properties. Apart from its use in medicine, black cumin is used as a filler in the production of new and eco-friendly eco-composites to reduce the environmental pollution caused by petroleum-based classical polymer composite materials. In this study, bio-based thermoplastic polyurethane (TPU) polymer was used as a matrix and black cumin unmodified and modified with 3 different functionalized group silanes, was added as a filler and mixed in a twin-screw extruder, and biocomposite materials in the form of dog-bones were produced by injection molding. Black cumin powders were analyzed by Fourier-transform infrared-attenuated total reflection (FTIR/ATR), field effect scanning electron microscopy (FESEM), and thermogravimetric analysis (TGA), while the mechanical, tribological, morphological, thermal, thermo-mechanical, melt flow index, and biological properties of the produced biocomposites were characterized. According to the results obtained, it was seen that surface treatment of the black cumin with silane both improved the biodegradability and other properties of eco-composites. Among thermoplastic polyurethane-based eco-composites, surface modification of black cumin with 3-aminopropyltriethoxysilane had the lowest water absorption capacity of 8% and also the highest abrasion resistance and an improvement of 88.5%. It was observed that the eco-composite containing octyldecyl-modified black cumin had the lowest MFI value of 26, the best biodegradability among the surface-modified eco-composites, the tensile strength of 14.5 MPa, and the highest value compared to other eco-composites. Epoxy-silane modifier yields optimum results in terms of thermal and thermo-mechanical analysis.
Keywords: Lignocellulose; Black Cumin; Thermoplastic Polyurethane